Tunnel oxide passivating contact enabled by polysilicon on ultra-thin SiO2 for advanced silicon radiation detectors - Yuguo Tao; Mackenzie Duce; Anna Erickson (Scientific Reports, 2024)
Abstract Conventional silicon junction detectors encounter significant carrier recombination within the heavily doped p + and n + layers, as well as beneath the metal contact regions, creating the so-called “dead layers”, especially on the detector side. In this study, we present the tunnel oxide passivating contact with doped polysilicon on oxide, which demonstrates exceptional surface passivation and carrier selectivity. The key innovation lies in an ultra-thin (~ 1.5 nm) interfacial oxide layer that facilitates efficient majority carrier transportation via tunneling while effectively block minority carriers. Remarkably low saturation current densities, ranging from 5 to 10 fA/cm2 even with the metal contact, underscore the superiority of both n-type and p-type tunnel oxide passivating contacts. In contrast, conventional p–n junction or high-low junction exhibit saturation current densities ranging from 10 to 90 fA/cm2 in the studied p + and n + layers with surface passivation schemes due to Auger recombination and surface recombination, and 1000–6000 fA/cm2 with metal contacts due to intense metal-induced recombination at the interface. These findings indicate the potential and superiority of implementing n-type tunnel oxide passivating contact on the detector side and p-type contact on the back side for advanced silicon radiation detectors. This approach would enable thorough collection of generated charge carriers along the track of incident ionizing radiation particles, leading to improved energy resolution and reduced noise levels.